Selective Sphingosine-1-Phosphate Receptor 1 Modulation Attenuates Experimental Intracerebral Hemorrhage. Issue 7 (July 2016) - Sun, Na; Shen, Yi; Han, Wei; Shi, Kaibin; Wood, Kristofer; Fu, Ying; Hao, Junwei; Liu, Qiang; Sheth, Kevin N.; Huang, DeRen; Shi, Fu-Dong
Abstract : Background and Purpose—: Preclinical studies and a proof-of-concept clinical study have shown that sphingosine-1-phosphate receptor (S1PR) modulator, fingolimod, improves the clinical outcome of intracerebral hemorrhage (ICH). However, the specific subtype of the S1PRs through which immune modulation provides protection in ICH remains unclear. In addition, fingolimod-induced adverse effects could limit its use in patients with stroke because of interactions with other S1PR subtypes, particularly with S1PR3. RP101075 is a selective S1PR1 agonist with superior cardiovascular safety profile. In this study, we investigated the impact of RP101075 treatment in a mouse model of ICH. Methods—: ICH was induced by injection of autologous blood in 294 male C57BL/6J and Rag2 −/− mice. ICH mice randomly received vehicle, RP101075, or RP101075 plus S1PR1 antagonist W146 by daily oral gavage for three consecutive days, starting from 30 minutes after surgery. Neurodeficits, brain edema, brain infiltration of immune cells, blood–brain barrier integrity, and cell death were assessed after ICH. Results—: RP101075 significantly attenuated neurological deficits and reduced brain edema in ICH mice. W146 blocked the effects of RP101075 on neurodeficits and brain edema. RP101075 reduced the counts of brain-infiltrating lymphocytes, neutrophils, and microglia, as well as cytokine expression after ICH. Enhanced blood–brain barrier integrity and alleviated neuronal death were also seen in ICH mice after RP101075 treatment. Conclusions—: S1PR1 modulation via RP101075 provides protection in experimental ICH. Together with the advantageous pharmacological features of RP101075, these results warrant further investigations of its mechanisms of action and translational values in ICH patients. Abstract : Supplemental Digital Content is available in the text.